Penjatuhan Pidana Bagi Pelaku Tindak Pidana Pelecehan Seksual Fisik (Studi Putusan Nomor 533/Pid.B/2024/Pn.Sda) - Diah Rahmania Arofah; Yana Indawati (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Criminal acts, as a general concept, encompass various crimes, including sexual violence, which often occurs in social life. These crimes are a concern because they constitute serious violations of human values and individual rights, and are even categorized as crimes against humanity in international law. Sexual violence can take many forms, including sexual harassment, which can affect anyone, although women are often the most vulnerable group to this violation. This study aims to explain the fulfillment of the elements of the crime of physical sexual harassment and the basis of consideration used by judges in imposing criminal penalties in Decision Number 533/Pid.B/2024/PN.Sda. This study is normative juridical in nature, using secondary data with qualitative processing, as well as a legislative, case, and conceptual approach. The results of the study show that the perpetrator was found guilty as charged by the public prosecutor, but not in accordance with the principle of lex specialis derogate legi generalis because the judge disregarded the specific rules. The study also reveals the judges' considerations, both legal and non-legal, in determining the severity of the punishment in the verdict.